Tectonic Collision as important factor controlling hydrocarbon generation in Eastern Indonesia Basins : Case study in Timor-Tanimbar Trough - Toha, Budianto (2013)
The present Eastern Indonesia is largely a result of the Neogene subduction of the NW continental margin of Australian plate and its associated shelf, beneath the oceanic Banda Sea plate. The Tanimbar Islands are interpreted as the most distal parts of the Australian passive margin deformed and uplifted a foldbelt during the arc-continent collision. This collision complex is bounded to the south and east by Timor and Tanimbar Trough, interpreted as bathymetric depression (foredeep) within the Australian margin. The tectonic processes are further influenced by Late Miocene to Recent, strike-slip tectonics generated by the westward moving Pacific Plate.